FRET‐based imaging of intracellular ATP in organotypic brain slices. Issue 8 (1st December 2018) - Lerchundi, Rodrigo; Kafitz, Karl W.; Winkler, Ulrike; Färfers, Marcel; Hirrlinger, Johannes; Rose, Christine R.
Abstract: Active neurons require a substantial amount of adenosine triphosphate (ATP) to re‐establish ion gradients degraded by ion flux across their plasma membranes. Despite this fact, neurons, in contrast to astrocytes, do not contain any significant stores of energy substrates. Recent work has provided evidence for a neuro‐metabolic coupling between both cell types, in which increased glycolysis and lactate production in astrocytes support neuronal metabolism. Here, we established the cell type‐specific expression of the Förster resonance energy transfer (FRET) based nanosensor ATeam1.03 YEMK ("Ateam") for dynamic measurement of changes in intracellular ATP levels in organotypic brain tissue slices. To this end, adeno‐associated viral vectors coding for Ateam, driven by either the synapsin‐ or glial fibrillary acidic protein (GFAP) promoter were employed for specific transduction of neurons or astrocytes, respectively. Chemical ischemia, induced by perfusion of tissue slices with metabolic inhibitors of cellular glycolysis and mitochondrial respiration, resulted in a rapid decrease in the cellular Ateam signal to a new, low level, indicating nominal depletion of intracellular ATP. Increasing the extracellular potassium concentration to 8 mM, thereby mimicking the release of potassium from active neurons, did not alter ATP levels in neurons. It, however, caused in an increase in ATP levels in astrocytes, a result which was confirmed in acutely isolated tissue slices. In summary, our results demonstrate that organotypic cultured slices are a reliable tool for FRET‐based dynamic imaging of ATP in neurons and astrocytes. They moreover provide evidence for an increased ATP synthesis in astrocytes, but not neurons, during periods of elevated extracellular potassium concentrations. Abstract : Expression of genetically encoded nanosensors in brain tissue slices allows dynamic, FRET‐based imaging of changes in intracellular ATP levels. Using this technique, we demonstrate that ATP levels in neurons and astrocytes change differently upon increases in the extracellular potassium concentration.